Preferensi Muzakki Dalam Memilih Membayar Zakat di Lembaga Zakat Formal - Ma'fiyah, Ma'fiyah; Yughi, Sheila Ardilla; Awaludin, Taufik (AL-FALAH : Journal of Islamic Economics, 2018)
This study aims to identify the dominant factors that influence muzakki in choosing to pay zakat to formal zakat institutions in aspects of individual and institutional perspectives and provide recommendations related to efforts to increase the collection of zakat funds from the community. The research method used is descriptive, factor and mean analysis. Descriptive analysis was used to explain the demographics of respondents while factor analysis and mean analysis were used to obtain the dominant factors affecting muzakki in paying zakat to the Formal Zakat Institution. The results of the study get in the aspect of individual perspective that predominantly influence muzakki paying zakat to formal zakat institutions sequentially is the knowledge of zakat, faith and religiosity as well as awareness and trust while in the perspective of institutional perspectives are management credibility, institutional credibility, service quality and socialization. The advice given is formal institution zakat amil must professionally manage the institution and have standard operating procedures especially related to the procedure of receiving zakat and commitment to implement it properly. In addition, zakat institutions must inform the general profile of the institution and report on zakat funds regularly. Zakat institutions also have the best online payment facilities.